Feasibility of endoscopic hand suturing on rectal anastomoses in ex vivo porcine models - Eriko Koizumi (Nature Portfolio, 2021)
Abstract Prevention of postoperative anastomotic leakage in rectal surgery is still required. This study investigated the feasibility of endoscopic hand suturing (EHS) on rectal anastomosis ex vivo. By using isolated porcine colon, we prepared ten anastomoses 6–10 cm from the virtual anus. Then, we sutured anastomoses intraluminally by EHS, which involved a continuous suturing method in 5 cases and a nodule suturing method with extra corporeal ligation in 5 cases. Completeness of suturing, number of stitches, procedure time and presence of stenosis were investigated. Furthermore, the degree of stenosis was compared between the two suturing methods. In all cases, EHS were successfully completed. The median number of stitches and procedure time was 8 and 5.8 min, respectively. Stenosis was created in all continuous suturing cases whereas none was seen in nodule suturing cases. The shortening rate was significantly greater in the continuous suturing method than in the nodule suturing method. Intraluminal reinforcement of rectal anastomosis by EHS using nodule suturing with extra corporeal ligation is feasible without stenosis, which may be helpful as a countermeasure against possible postoperative anastomotic leakage in rectal surgery.